Role of Microglia TLRs in Neurodegeneration - Fiebich, Bernd L.; Batista, Carla Ribeiro Alvares; Saliba, Soraya Wilke; Yousif, Nizar M.; de Oliveira, Antonio Carlos Pinheiro (Frontiers in Cellular Neuroscience, 2018)
Toll-like receptors (TLRs) are a group of receptors widely distributed in the organism. In the central nervous system, they are expressed in neurons, astrocytes, and microglia. Although their involvement in immunity is notorious, different papers have demonstrated their roles in physiological and pathological conditions, including neurodegeneration. There is increasing evidence of an involvement of TLRs, especially TLR2, 4, and 9 in neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). In this sense, their expression in microglia might modulate the activity of these cells, which in turn, lead to protective or deleterious effects over neurons and other cells. Therefore, TLRs might mediate the link between inflammation and neurodegenerative diseases. However, further studies have to be performed to elucidate the role of the other TLRs in these diseases and to further prove and confirm the pathophysiological role of all TLRs in neurodegeneration. In this paper, we revise and summarize the current knowledge regarding the role of TLRs in neurodegeneration with the focus on the possible functions of these receptors in microglia.